Evaluasi Keberhasilan Pelaksanaan Infrastruktur Jalan Desa Terkait dengan Pendanaan Dana Desa Kabupaten Pubalingga - Luthfi, Abdullah; Ismiyati, I; Hermawan, Ferry (Jurnal Pembangunan Wilayah dan Kota, 2020)
The implementation of the Village Fund policy made a very significant change, the villages which had previously received a very limited budget were managed centrally by government agencies on top of which villages now get a substantial budget and are given the authority to manage independently. Village Funds for physical development realized in 2015, 2016 and 2017 that are felt transparently, do not meet the quality of infrastructure in supporting facilities and infrastructure. This study aims to evaluate the successful implementation of village road infrastructure related to village funding. The location of this research is Gondang Village, Kertanegara Village and Karanggambas Village, Purbalingga Regency. The data analysis technique used is data analysis with quantitative and qualitative methods with steps of data collection, data reduction, data presentation and conclusion drawing. The results of this study show that (1) Village planning in the research location is not fully in accordance with Permendagri Number 114 of 2014, (2) the highest level of road damage in Karanggambas Village (16.94%), the biggest 2016 and 2017 road damage in the village Gondang (10.73% and 17.77%) (3) commitment and quality of human resources affect the successful implementation of infrastructure planning and development, (4) Implementation of Village Funds in terms of benefits has been felt by the community in meeting basic infrastructure needs, but not fully implemented. said to be successful, (5) the level of maintenance of damage to village road infrastructure is still low.